ANCA-associated vasculitis and severe proximal muscle weakness. Issue 3 (4th May 2021) - Dutcher, Jordan S.; Bui, Albert; Ibe, Tochukwu A.; Umadat, Goyal; Harper, Eugene P.; Middlebrooks, Erik H.; Mohseni, Michael M.; Phillips, Michael B.
Abstract: ANCA-associated vasculitis is a multiorgan autoimmune inflammatory disease that has a heterogeneous clinical presentation. Our case report provides additional evidence supporting the association between granulomatosis with polyangiitis and myositis. In our patient with proximal muscle weakness and pain, a normal creatine kinase and lack of antibodies to muscular fiber units ruled out primary myositis. Distinct magnetic resonance imaging of the brain within the deep gray matter in addition to positive serologies were consistent with a diagnosis of granulomatosis with polyangiitis. ANCA-associated vasculitis, specifically granulomatosis with polyangiitis, may be overlooked if musculoskeletal manifestations are the presenting symptoms. Prompt and aggressive treatment prevented this patient from experiencing multiorgan failure.